Nutraceuticals for the Treatment of IBD: Current Progress and Future Directions - Ban, Quan-Yao; Liu, Mei; Ding, Ning; Chen, Ying; Lin, Qiong; Zha, Juan-Min; He, Wei-Qi (Frontiers in Nutrition, 2022)
Inflammatory bowel disease (IBD) is a chronic relapsing-remitting inflammatory disease of the gastrointestinal tract. Patients are usually diagnosed in adolescence and early adulthood and need lifelong treatment. In recent years, it has been found that diet plays an important role in the pathogenesis of IBD. Diet can change intestinal barrier function, affect the structure and function of intestinal flora, and promote immune disorder, thus promoting inflammation. Many patients believe that diet plays a role in the onset and treatment of the disease and changes their diet spontaneously. This review provides some insights into how nutraceuticals regulate intestinal immune homeostasis and improve intestinal barrier function. We reviewed the research results of dietary fiber, polyphenols, bioactive peptides, and other nutraceuticals in the prevention and treatment of IBD and sought better alternative or supplementary treatment methods for IBD patients.